2015
DOI: 10.1103/physrevapplied.3.044017
|View full text |Cite
|
Sign up to set email alerts
|

Current Filamentation in LargeBi2Sr2CaCu2O8

Abstract: We have studied the self-heating of a large stack of Bi 2 Sr 2 CaCu 2 O 8+δ intrinsic Josephson junctions, of a configuration designed for THz generation. We find good qualitative agreement between direct thermoluminescent measurements of the device surface temperature and low-temperature scanning laser microscopy images. In particular, the two techniques both reveal a novel mode of thermal instability through the asymmetric nucleation of a small hot-spot near a corner/edge of the sample. This behavior conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…their crystalline c-axis) described above. Not only do they experimentally show complex inhomogeneous self-heating behavior 5,6,7,8,9,10,11 it has been theoretically predicted that this may be beneficial for THz power emission 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…their crystalline c-axis) described above. Not only do they experimentally show complex inhomogeneous self-heating behavior 5,6,7,8,9,10,11 it has been theoretically predicted that this may be beneficial for THz power emission 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown by Dieckmann et al 69 that this technique, lowtemperature scanning laser microscopy (LTSLM), delivers results that are equivalent to LTSEM. LTSLM has, among others, been applied to research on superconductors 32,34,70,71 , the quantum Hall effect 72 , spintronics 73,74 and spin-caloritronics 75 . The LTSPM can be operated in LTSLM mode to gain information on the electric trans- port properties of a sample.…”
Section: Imaging Of Electric Transport Propertiesmentioning
confidence: 99%
“…The confocal laser scanning microscope offers an additional imaging mechanism: a beam-induced voltage across a currentbiased sample can be generated by the local perturbation of the laser beam. This beam-induced voltage can be used to extract local information on the electric transport properties of the sample [30][31][32][33][34] . While several examples of low-temperature widefield [35][36][37] and laser scanning polarizing microscopes [38][39][40] have been published, the instrument presented here stands out with regard to the versatility offered by combining widefield and confocal laser scanning imaging modes, the accessible temperature range, as well as the very high lateral resolution it provides at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, the tunability of a single RTD source is 5% at best [19]. Previous studies have shown that the thermal management of emitting sources is a key requirement for controlling their characteristics [20,21,22,23,24,25,26,27,28,29,30,31,32,33,34]. Previously, radiation above 1 THz was achieved by an improved cooling technique [27].…”
Section: Introductionmentioning
confidence: 99%